Evaluation of a rapid immunochromatographic test for detection of distinct variants of Klebsiella pneumoniae carbapenemase (KPC) in Enterobacteriaceae - Ramos, Ana C. [UNIFESP] (2017)
The rapid detection of KPC-producing Enterobacteriaceae by microbiology laboratories has been required for infectious control programs. Herein we evaluated the performance of a novel immunochromatographic test for detecting KPC-2-, KPC-3-, KPC-4-, KPC-6-, KPC-7-, KPC-8-, and KPC-11-producing isolates and the influence of different growth media on the test performance.